Design of “Kayangan Api Park” at Bojonegoro as Facilities The 15 Th National Olympic Games - A. Tutut Subadyo; Junianto Junianto (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Kayangan Api Park (KAP) is a park dedicated to the 15 th National Olympic Games at Surabaya, East Java. This design is required to create new work architecture in the form of park design with a different concept. The methods used in the design KAP through two approaches including socio-cultural-historical such as interview then biophysical approaches such as observation, spatial analysis and analysis of the carrying capacity. Design KAP done on site with an area of 1500 m2 with basic concept and inspiring from Javanese local genius and local wisdom as spheres of art and culture in Indonesia. Design processes of KAP refer from step research and analysis, preliminary design and construction drawing with applicated of basic elements as landform, cultural and sociological approach, site development, building and plant material. KAP is a form of cultural park that can accommodate a variety of cultural activities in open space such as exhibition of the installation art work, sculpture, street art and other various work of cultural art. Finally design of KAP is creating a site plan, lay out plan, perspective, sequence illustration, and explanation about detail engineering design.